Exploring the Issues in the Social Interaction between Immigrant and Host Communities - Ristiandar, Dia; Nurchayati, Nurchayati (Character Jurnal Penelitian Psikologi, 2023)
Using the ethnographic approach, this qualitative psychological research explored the issues in the social interaction between immigrants and the host community. Research data was collected through field research, using interviews with and observations of migrants and locals. Open coding was employed to crystallize the resulting data into meaningful categories. This research identified three central issues in immigrant-local social encounter. They were societal stereotypes, intergroup prejudices, and ethnocentrism. These issues resulted from societal categories, social identities, and the particular ways in which people tackled the challenges of social interaction.